Silicon Micromachining for High Performance Passive Structures at W Band - B. Guillon; K. Grenier; T. Parra; P. Pons; D. Cros; P. Blondy; J. Graffeuil; J. L. Cazaux; R. Plana (Active and Passive Electronic Components)
This paper presents a micromachined technology allowing the realization of very high aspect ratio millimeter-wave circuits. Appropriate 3D electromagnetic simulations based on the finite element method have been implemented to design the circuits. Coplanar transmission lines featuring loss level in the 2 dB range up to 105 GHz have been realized. An original silicon micromachined cavity using the whispering gallery modes properties has been realized achieving a quality factor close to 10,000 range at 95 GHz.